Constant active power control circuit of single phase alternating current fan and water pump - SU BO (2013)
Disclosed is a constant active power control circuit of a single phase alternating current fan and a water pump. The constant active power control circuit is applied to fields of products of gas wall-hanging stoves, gas water heaters, gas air heaters, biomass furnaces, solar energy hot water work stations, room air renewal systems (new air systems) and the like. The constant active power control circuit comprises a floating ground direct-current power supply, an alternating voltage zero-cross detection portion, an alternating voltage sampling and amplifying circuit, a motor current sampling and amplifying circuit, a motor driving circuit, a micro controller unit (MCU) and a serial communication separation circuit. The micro controller obtains a current target work power value of a fan or a water pump through serial communications and performs proportion integration differentiation (PID) algorithm control according to a current actual work power value of a motor to achieve the constant active power control of